PEMBELAJARAN TRANSFORMATIF DALAM PENDIDIKAN IPA: A LITERATURE REVIEW OF EMPIRICAL RESEARCH - Fandi Ahmad; Nur Indah Sari (Program Studi Tadris IPA IAIN Parepare, 2026)
21st century science education must be able to foster critical and reflective scientific literacy through transformative learning. This research aims to synthesize, analyze and evaluate the state of the art from empirical research related to the application of transformative learning in science education. The research method used was a Systematic Literature Review following PRISMA guidelines for 15 selected articles. The research results reveal that the disorienting dilemma triggered by the theory-practice gap, socio-scientific issues, and visceral experiences in the wild are the main catalysts for transformation. The process of critical reflection plays an important role in bridging epistemological beliefs with field realities, which results in deep changes in self-identity, global perspective, and self-empowerment in environmental action. The results of the literature analysis show that transformative learning has succeeded in shifting the science education paradigm from simply memorizing concepts to developing critical and reflective scientific literacy. This is essential for forming students into independent individuals who are socially responsible for global issues such as climate change and sustainability.